THEATRE: Ngugi and Revolution in The Trial of Dedan Kimathi - Ordu, Stanley; Odukwu, Better (Journal of Social, Humanity, and Education, 2022)
Purpose: The purpose of this work is to explore The Trial of Dedan Kimathi through the lenses of revolutionary aesthetics and class stratification as a kind of socio-literary participation. The book's exploration of the notion of revolution delves deeply into topics of tyranny, exploitation, and poverty. Numerous consequences emerged from the examination of the selected text. Research methodology: Theoretical Framework: Marxist literary theory guided the analysis of the study. Results: This research documents European aggression, economic exploitation of Africans, taxes and forced labor, the degradation of people's humanity, a decrease in human capital, the depths of hunger and poverty, and Africans' reaction and resistance to these terrible conditions. In order to come up with a long-term solution, we need to understand and agree that Africans have been oppressed and treated cruelly in the past. Limitations: The study is limited to the play The Trial of Dedan Kimathi. Contribution: The Marxist philosophy has been used as a weapon of change in order to bring about revolutions. Through the medium of theater, people may be entertained, educated, and made more aware.